The asynchronous motor one-dimensional analysis - Simone, G. A.; Creppe, R. C.; Souza, C. R.; IEEE (I E E E, 1997)
An application of the linear machine one-dimensional analysis method to the modeling of a conventional asynchronous induction motor, considered as a particular case of linear and sectorial machines, is described. A mathematical model for the calculation of the propulsive force developed by this motor, taking into account the transversal edge effect, is derived from the application of the one-dimensional theory and presented in this paper. As an application example, an induction motor is analyzed by means of the one-dimensional theory.
Keywords: one-dimensional theory; linear machine modeling; sector-motor